Długi cień Tolkiena - Gołuński, Mirosław (Śląskie Studia Polonistyczne, 2014)
In the review of the book W cieniu białego drzewa. Powieść fantasy w XX wieku by Tomasz Z. Majkowski, the author argues its theses, indicating at significant shortcomings of the publication. At the same time, he presents his own ideas on fantasy convention research. He points to important categories of research of novels written in this style, not included by Majkowski: the relation to mythologies and the necessity of utilizing the history of ideas, should one want to create its historical and literary compendium.